Use of inpatient rehabilitation for cancer patients in Switzerland: who undergoes cancer rehabilitation? (Swiss Medical Weekly, 2015)
QUESTION UNDER STUDY: Rehabilitation for cancer patients aims to reduce physical disability and mental distress resulting from the disease and its treatment. However, little is known about the use of cancer inpatient rehabilitation in Switzerland in relation to sociodemographic and medical characteristics. The main purpose of this study was to evaluate whether there are differences in sociodemographic and medical characteristics between patients who underwent inpatient rehabilitation (users) and those who did not (nonusers). METHODS: A total of 238 cancer patients from the University Hospital Zurich were included. The sociodemographic and medical characteristics of inpatient rehabilitation users were assessed and compared with those of nonusers. We analysed the differences between inpatient rehabilitation users and nonusers. RESULTS: Of the patients included, 101 (42.4%) used inpatient rehabilitation. They were less likely to be employed (p = 0.029), stayed longer in hospital (p